Pyroptosis-Related lncRNA Prognostic Model for Renal Cancer Contributes to Immunodiagnosis and Immunotherapy - Zhou, Xuan; Yao, Liangyu; Zhou, Xiang; Cong, Rong; Luan, Jiaochen; Wei, Xiyi; Zhang, Xu; Song, Ninghong (Frontiers in Oncology, 2022)
Background: Renal clear cell cancer(ccRCC) is one of the most common cancers in humans. Thus, we aimed to construct a risk model to predict the prognosis of ccRCC effectively. Methods: We downloaded RNA sequencing (RNA-seq) data and clinical information of 539 kidney renal clear cell carcinoma (KIRC) patients and 72 normal humans from The Cancer Genome Atlas (TCGA) database and divided the data into training and testing groups randomly. Pyroptosis-related lncRNAs (PRLs) were obtained through Pearson correlation between pyroptosis genes and all lncRNAs (p<0.05, coeff >0.3). Then univariate and multivariate cox regression analyses were performed to select suitable lncRNAs. Next, a novel signature was constructed and evaluated by survival analysis and ROC analysis. The same observation applies to the testing group to validate the value of the signature. By gene set enrichment analysis (GSEA) we predicted the underlying signaling pathway. Furthermore, we calculated immune cells infiltration, immune checkpoint, the T cell receptor/B cell receptor (TCR/BCR), SNV, TIDE scores by TCGA database. We also validate our model with an immunotherapy cohort. Finally, the expression of PRLs was validated by quantitative PCR (qPCR). Results: We constructed a prognostic signature comprised of six key lncRNAs (U62317.1, MIR193BHG, LINC02027, AC121338.2, AC005785.1, AC156455.1), significantly predict different overall survival (OS) rates. The efficiency was demonstrated using the receiver operating characteristic (ROC) curve. The signature was observed to be an independent prognostic factor in cohorts. In addition, we found the PRLs, promoting the tumor progression via immune-related pathways revealed in GSEA. Furthermore, the TCR, BCR, and SNV data were retrieved to screen immune features, and immune cell scores were calculated to measure the effect of the immune microenvironment on the risk model, indicating that high and low-risk score have different immune statuses. Then, the TIDE algorithm was used to predict the immune checkpoint blockade (ICB) response of our model, and subclass mapping was used to verify our model in another immunotherapy cohort data. Finally, qPCR validate the PRLs in cell lines. Conclusion: This study provided a new risk model to evaluate ccRCC and may be pyroptosis-related therapeutic targets in the clinic.